Evaluation of Soybean Hulls as Replacement of Energy Concentrates: Effects on Intake, Growth Performance and Selected Blood Metabolites of Male Sahiwal Calves - Nisar, Awais Bin; Pasha, Talat Naseer; Rashid, Muhammad Afzal; Bilal, Muhammad; Malik, Muhammad Irfan; Naqvi, Zahra Batool (Insights in Animal Science, 2024)
The objective of this study was to evaluate the effects of replacing conventional energy sources (corn grain and wheat bran) with soyhulls on the growth performance of Sahiwal calves. Fifteen growing Sahiwal male calves weighing approximately 110 ± 2 kg were selected, blocked by body weight, and randomly assigned to one of three dietary treatments (5 calves/treatment) in a randomized complete block design. The treatments consisted of three concentrate diets: control (SH0, without soyhulls), SH18 (soyhulls replacing 30% of conventional energy sources), and SH36 (soyhulls replacing 60% of conventional energy sources). All diets were isonitrogenous with 13.5% crude protein (CP) and were fed as a total mixed ration (TMR) comprising 60% concentrate, 32% silage, and 8% Rhodes grass hay on a dry matter basis. Body weight was recorded weekly. Three animals per treatment were selected for an apparent digestibility trial using acid-insoluble ash as a marker. Results indicated a numerical increase in dry matter intake (DMI) with higher soyhull levels. Digestibility of NDF, ADF, DM, and OM increased linearly (p ≤ 0.05) with increasing soyhulls in the diets. Total weight gain was 129 kg for SH0, 128 kg for SH18, and 133 kg for SH36. The average daily gain (ADG) was slightly more in the SH36 group (1.19 kg) than the SH0 group (1.15 kg). Cost per unit gain, blood glucose, and blood urea nitrogen (BUN) levels were similar (p > 0.05) among the treatments. In conclusion, the study demonstrated that soyhulls can be an effective alternative energy source to the corn grain and wheat bran, with similar growth performance and cost per unit gain with the additional benefits of greater dry matter intake and nutrient digestibility in male Sahiwal calves.
Keywords: soyhulls; energy source; calf performance